Down syndrome regression disorder, a case series: Clinical characterization and therapeutic approaches - Bonne, Sidney; Iftimovici, Anton; Mircher, Clotilde; Conte, Martine; Louveau, Cécile; Legrand, Adrien; Danset-Alexandre, Charlotte; Cannarsa, Costanza; Debril, Alexis; Consoli, Angèle; Krebs, Marie-Odile; Ellul, Pierre; et al. (Frontiers in Neuroscience, 2023)
Down syndrome (DS) is one of the most frequent genetic disorders and represents the first cause of intellectual disability of genetic origin. While the majority of patients with DS follow a harmonious evolution, an unusual neurodevelopmental regression may occur, distinct from that described in the context of autism spectrum disorders, called Down Syndrome Regression Disorder (DSRD). Based on four patients, two males and two females, with age range between 20-24, treated at the Reference Center for Rare Psychiatric Disorders of the GHU Paris Psychiatry and Neurosciences (Pôle hospitalo-universitaire d'Évaluation Prévention et Innovation Thérapeutique - PEPIT), we describe this syndrome, discuss its etiologies and propose therapeutic strategies. DSRD often occurs in late adolescence. There is a sudden onset of language disorders, loss of autonomy and daily living skills, as well as behavioral symptoms such as depression, psychosis, or catatonia. These symptoms are nonspecific and lead to an overlap with other diagnostic categories, thus complicating diagnosis. The etiologies of the syndrome are not clearly identified but certain predispositions of patients with trisomy 21 have suggested an underlying immune-mediated mechanism. Symptomatic therapeutic approaches (serotonergic antidepressants, atypical antipsychotics, benzodiazepines) were not effective, and generally associated with poor tolerance. Etiological treatments, including anti-inflammatory drugs and corticosteroids, led to partial or good recovery in the four cases. Early recognition of regressive symptoms and rapid implementation of adapted treatments are required to improve the quality of life of patients and their families.